1990
DOI: 10.1007/bf00931236
|View full text |Cite
|
Sign up to set email alerts
|

The psychological sequelae of disaster stress prospectively and retrospectively evaluated

Abstract: Aimed to document the psychological sequelae of a disaster in the adult (17-68 years) population of the Caribbean island of Puerto Rico, by surveying 912 persons (including 375 previously interviewed) with a Spanish version of the Diagnostic Interview Schedule. A rigorous methodology, which included both retrospective and prospective designs, was used, enabled by the occurrence of a catastrophic disaster only a year after a comprehensive survey was completed. Framed in a stress theoretical perspective, disaste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
88
0
3

Year Published

1994
1994
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(95 citation statements)
references
References 16 publications
4
88
0
3
Order By: Relevance
“…Because an island-wide mentalhealth survey had only recently been completed, it was possible to assess the storm's psychological impact prospectively by comparing predisaster and postdisaster adjustment. In summarizing the results of such an analysis, Bravo, Rubio-Stipec, Canio, Woodbury, and Ribera (1990) concluded that although the storm did result in increased depression, somatic complaints, and PTSD symptoms, ''all the effects, however, were relatively small, suggesting that most disaster victims were rather resilient to the development of new psychological symptoms'' (p. 662).…”
Section: Toward An Individual-differences Approachmentioning
confidence: 99%
“…Because an island-wide mentalhealth survey had only recently been completed, it was possible to assess the storm's psychological impact prospectively by comparing predisaster and postdisaster adjustment. In summarizing the results of such an analysis, Bravo, Rubio-Stipec, Canio, Woodbury, and Ribera (1990) concluded that although the storm did result in increased depression, somatic complaints, and PTSD symptoms, ''all the effects, however, were relatively small, suggesting that most disaster victims were rather resilient to the development of new psychological symptoms'' (p. 662).…”
Section: Toward An Individual-differences Approachmentioning
confidence: 99%
“…In the first study, population data on psychiatric disorders obtained a year before the occurrence of torrential rains and mudslides in Puerto Rico (43)(44)(45) were used in a prospective examination of predisaster and postdisaster somatoform symptoms in the unexposed population compared with those of the disaster-exposed group. Disaster exposure was significantly associated with development of new, medically unexplained physical symptoms not present before the disaster, especially gastrointestinal and pseudoneurological symptoms.…”
Section: Somatization In Disaster Literaturementioning
confidence: 99%
“…In our study, the consistence of results with other biophysical reports and the congruence between the magnitude of transformations and the impacts on levels of well-being in different geographical sectors, suggests the validity of respondents' recall. Natural disasters are unexpected and it is unlikely to plan for diachronic designs to count on systematic preevent information (Bravo et al 1990). Therefore, retrospectively assessing people's experiences represents a practicable method in the face of natural disasters and abrupt ecosystem transformations.…”
Section: Discussionmentioning
confidence: 99%